Variations in the milk lipidomic profile of lactating dairy cows fed the diets containing alfalfa hay versus alfalfa silage - Kaizhen Liu; Meiqing Chen; Guoxin Huang; Chuanyou Su; Wenhao Tang; Ning Li; Jiyong Yang; Xufang Wu; Boxue Si; Shengguo Zhao; Nan Zheng; Yangdong Zhang; et al. (Animal Nutrition)
Alfalfa is primarily stored as silage or hay in livestock production. Previous research has shown that the storage method of grass significantly influences milk composition. This study aimed to investigate milk production performance and lipid composition in dairy cows fed diets consisting of alfalfa hay or alfalfa silage as roughage. Forty-two mid-lactation Holstein dairy cows were selected and randomly divided into three groups, each receiving a total mixed ration consisting of alfalfa hay (AH), 50% alfalfa silage + 50% alfalfa hay (AHAS), or alfalfa silage (AS). The results showed that milk fat content (P = 0.049) and milk fat yield (P < 0.001) were significantly higher in the AH and AHAS groups compared to the AH group. With increased supplementation of alfalfa silage in the diet, ω-3 polyunsaturated fatty acid content increased significantly (P < 0.001), while ω-6 polyunsaturated fatty acid content (P = 0.007) and the ratio of ω-6 to ω-3 polyunsaturated fatty acids decreased (P < 0.001). The contents of sphingomyelins, phosphatidylserines, phosphatidylethanolamines, and phosphatidylglycerols in the AHAS and AS samples were higher than in the AH samples, although the differences were not statistically significant. Additionally, the content of phosphatidylcholines was significantly higher in the AS group compared to the AH group (P = 0.032). In conclusion, feeding dairy cows a diet consisting of alfalfa silage can increase the major phospholipid content and polyunsaturated fatty acid composition in raw milk, which is more conducive to human health. These findings provide valuable insights into the benefits of alfalfa silage for dairy cows.